Studi tentang polimorfisme ulat sutera F1 hibrid hasil persilangan ras Jepang dan ras Cina yang berasal dari pusat pembibitan Soppeng dan Temanggung dengan menggunakan enzim restriksi Pst1 dan EcoR1 - Nur Cholis (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
There were diffferent performance between silkworms breeded in Soppeng and Temanggung. There might be different proportion of parenstock and environment which causing polymorphism. This experiment was to know the genetic band pattern as the effect of the silkworm origin to the genetic characteristics. RFLP method was applied by using restriction enzymes of Pst1 and EcoR1. Based on DNA running by RFLP method using those enzymes, there was no different DNA slice fragment, either between breeding site or genetic polymorphism of each breeding site. This may be caused by the mutation happened in position DNA arrangement which was not recognized by the two enzymes